Thromboembolic Rates Are Similar Between Intensive Care Unit and Nonintensive Care Unit Hospitalized Patients With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): A Retrospective Cohort Study. (November 2021) - Worth, Heidi; Helmlinger, Kasey; Raj, Renju; Heidel, Eric; Lands, Ronald
High rates of thromboembolic events have been described in intensive care unit (ICU) patients. Data regarding thromboembolic events in all hospitalized patients has been less frequently reported, raising concerns that thromboembolic events in non-ICU may be underrecognized. In addition, optimal anticoagulation type and dose is still unsettled at this time. This is a retrospective cohort study of 159 hospitalized patients with coronavirus disease 2019 (COVID-19) pneumonia during a 9-month period to determine an association between the frequency of thromboembolic rates and hospitalized patients with COVID-19. Secondary outcomes sought to investigate association of thromboembolic events with relation to place of admission, risk factors, anticoagulation, mortality, hospital length of stay, and discharge disposition. Among the cohort of 159 hospitalized patients who met criteria, 16 (10%) were diagnosed with a thromboembolic event. There were a total of 18 thromboembolic events with 12 venous and 6 arterial. Admission to the ICU was not associated with a higher frequency of thromboembolic events compared with non-ICU patients (37.5% vs 62.5%), p  = .71. Patients with a thromboembolic event had a significantly higher mortality compared with those with no thromboembolic event (37.5% vs 13.3%), p  = .012. Patients hospitalized with COVID-19 have increased rates of thromboembolic events, both venous and arterial, which contribute to a significant increase in mortality. However, the frequency of thromboembolism in patients admitted to the ICU was similar to events in non-ICU patients. We hope to increase awareness of the increased risk of hypercoagulability in all hospitalized patients with COVID-19 including non-ICU patients.